Obesiteit: 'n Teoretiese verkenning - L. Oelofse (AOSIS, 1984)
In a theoretical discussion on obesity the author shows that it is a complex condition, particularly as psychological factors play a significant role in its etiology. Various treatments exist including diet therapy, physical activity, medication, surgery, individual psychotherapy, behaviour therapy. It seems however that a group psychotherapeutic approach to treatment has the best prognostic value. Whatever method of treatment is used, however, physical as well as psychological aspects should be attended to.